Redistribution and Group Participation : Experimental Evidence from Africa and the UK - Fafchamps, Marcel; Vargas Hill, Ruth (Published by Oxford University Press on behalf of the World Bank, 2021)
We investigate whether the prospect of redistribution hinders the formation of efficiency-enhancing groups. We conduct an experiment in a Kenyan slum, Ugandan villages, and a UK university town. We test, in an anonymous setting with no feedback, whether subjects join a group that increases their endowment but exposes them to one of three redistributive actions: stealing, giving, or burning. We find that exposure to redistributive options among group members operates as a disincentive to join a group. This finding obtains under all three treatments—including when the pressure to redistribute is intrinsic. However the nature of the redistribution affects the magnitude of the impact. Giving has the least impact on the decision to join a group, while forced redistribution through stealing or burning acts as a much larger deterrent to group membership. These findings are common across all three subject pools, but African subjects are particularly reluctant to join a group in the burning treatment, indicating strong reluctance to expose themselves to destruction by others.